Pemahaman Etika dalam Pengelolaan Lembaga Eksekutif Dalam Politik Islam - Mulla Sadra; Wahyudi, A; Wahyudi, Kurniati (CV Putra Publisher, 2024)
The political and moral ethics of leadership, both in the Islamic context and outside of Islam, are greatly influenced by the attitudes and actions of those in power. A government that is just and based on ethical values ​​is important to learn from real experience and is based on the principles of justice in order to create peace. However, there is a knowledge gap regarding the application of ethical values ​​in leadership which can cause government instability. This research uses qualitative methods with a case study approach to analyze the application of political and moral ethics in leadership. The research results show that leaders who instill ethical and moral values ​​succeed in creating an atmosphere of happiness for their people, while leaders who ignore these values ​​experience a collapse in power. In addition, this research found that applying ethical values ​​in leadership can prevent chaos and increase government stability. The implications of this research show the importance of strengthening ethical and moral values ​​in leadership education to create a just and peaceful government.